2021
DOI: 10.1111/lcrp.12189
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic traits predict moral judgements in five moral domains: The mediating effect of unpleasantness

Abstract: Purpose The relationship between psychopathic traits and moral judgements has evoked passionate debates among researchers. Psychopathic traits have been characterized as risk factors for immoral behaviours in both non‐forensic and forensic populations; however, whether individuals with elevated psychopathic traits display atypical moral judgements has been controversial. Here, we aim to examine how psychopathic traits are related to moral judgements in five moral foundations (Care, Fairness, Loyalty, Authority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 75 publications
2
8
0
Order By: Relevance
“…Furthermore, we found that the EC from the posterior insula to the amygdala partially mediated the relationship between psychopathic traits and the concern with the Harm foundation. In conjunction with previous behavioral findings that emotion responses serve as a mediator in the relationship between psychopathic traits and morality (Glenn et al, 2009; Patil, 2015; Ye et al, 2021), the results here suggested that weakened capacity to integrate bodily-state information to emotional responses in individuals with elevated psychopathic traits in response to moral contexts accounts for their emotional shallowness, which partially contributes their atypical moral cognition. Importantly, the significant relationship between psychopathic traits and morality as well as the mediating role of the posterior insula-to-amygdala connectivity in the relationship was only observed in T-PTS and P-PTS, but not S-PTS.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Furthermore, we found that the EC from the posterior insula to the amygdala partially mediated the relationship between psychopathic traits and the concern with the Harm foundation. In conjunction with previous behavioral findings that emotion responses serve as a mediator in the relationship between psychopathic traits and morality (Glenn et al, 2009; Patil, 2015; Ye et al, 2021), the results here suggested that weakened capacity to integrate bodily-state information to emotional responses in individuals with elevated psychopathic traits in response to moral contexts accounts for their emotional shallowness, which partially contributes their atypical moral cognition. Importantly, the significant relationship between psychopathic traits and morality as well as the mediating role of the posterior insula-to-amygdala connectivity in the relationship was only observed in T-PTS and P-PTS, but not S-PTS.…”
Section: Discussionsupporting
confidence: 85%
“…In other words, those brain areas supporting emotional function might exert atypical influence on other brain regions during moral cognition for individuals with elevated psychopathic traits. Additionally, We expected our findings to be more pronounced for primary psychopathy than secondary psychopathy as recently we found psychopathic traits are correlated with moral judgments merely in primary psychopathy (Ye et al, 2021).…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations